2022
DOI: 10.31234/osf.io/bhpm5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neither nature nor nurture: Using extended pedigree data to understand indirect genetic effects on offspring educational outcomes

Abstract: Background: More highly educated parents tend to raise children who go on to complete more education themselves. Strong evidence for environmental transmission arises from the fact that offspring outcomes correlate to parental genotypes even when controlling for the offspring genotype. The process that gives rise to an environmentally mediated correlation between parental genotype and offspring education (“indirect genetic effects”) remains poorly understood. A key question is whether intergenerational transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…49,63 Likewise, the absence of passive rGE in our PA models appears to contradict recent molecular genetic evidence that suggests EA polygenic scores partly capture the effects of passive rGE. 29,30,[50][51][52][53] Here we stress that, while our bestfitting model was a PA model, our SH models did not fit the data significantly worse than our PA models. It's also possible that a mixed homogamy scenario, in which phenotypic assortment and social homogamy both play a role, might explain the data better than the PA and SH models compared in this study.…”
Section: Limitationsmentioning
confidence: 60%
See 2 more Smart Citations
“…49,63 Likewise, the absence of passive rGE in our PA models appears to contradict recent molecular genetic evidence that suggests EA polygenic scores partly capture the effects of passive rGE. 29,30,[50][51][52][53] Here we stress that, while our bestfitting model was a PA model, our SH models did not fit the data significantly worse than our PA models. It's also possible that a mixed homogamy scenario, in which phenotypic assortment and social homogamy both play a role, might explain the data better than the PA and SH models compared in this study.…”
Section: Limitationsmentioning
confidence: 60%
“…However, we also note that phenotypic assortment is expected to produce some of the molecular genetic effects that have been interpreted as passive rGE or "genetic nurture". 29,50,64 We briefly describe how phenotypic assortment can induce these effects in Supplementary Note 3.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects have been labelled 'indirect effects' or 'genetic nurture', but again only passive rGE is controlled in these analyses. Such indirect effects have so far only been found for cognitive traits, not behaviour problems (Willoughby et al, 2021) and it has been suggested that these effects of 'genetic nurture' are actually between-family stratification effects (Nivard et al, 2022). These analyses do not specify which environmental factors are responsible, but measured environments can be incorporated in this approach.…”
Section: Back To Familiesmentioning
confidence: 99%
“…Thus, the latest GWAS for educational attainment reports that, although 12‐16% of the variance in educational attainment among people of European ancestry is predicted by polygenic scores, less than 5% of the variance is due to direct genetic effects (Okbay et al., 2022 ). A recent paper, which Harden co‐authored, attempts to tease apart parental indirect effects and confounders by analyzing siblings of the parents as well as nuclear families; it concludes that much of the non‐direct genetic effects may be due to “dynastic stratification in environments relevant to success in school” (Nivard et al., 2022 ), a form of confounding.…”
Section: The Elision Of Different Types Of Gwasmentioning
confidence: 99%